Emerging Antimicrobial Resistance in Gram-Negative Pathogens: Protocol for a Pragmatic Cluster-Randomized Controlled Trial - Khan , Ahsan Raza; Iqbal , Mehwish (Journal of Society Medicine, 2026)
Introduction: Antimicrobial resistance among Gram-negative pathogens, including extended-spectrum β-lactamase (ESBL)-producing Enterobacterales and carbapenem-resistant Acinetobacter and Pseudomonas, is associated with high mortality and limited therapeutic options. Delayed initiation of effective antimicrobial therapy in bloodstream infections (BSIs) is consistently linked to adverse clinical outcomes. Although rapid diagnostic tests (RDTs) combined with antimicrobial stewardship (AS) improve the timeliness of therapy, high-quality evidence from resource-constrained settings remains limited. This study evaluates a pragmatic strategy integrating rapid diagnostics with stewardship to optimize early targeted therapy. Methods: This multicenter, parallel-group, pragmatic cluster randomized controlled trial includes 20 hospitals randomized to either an intervention bundle or standard care. The intervention comprises PCR-based pathogen and resistance gene identification, EUCAST rapid antimicrobial susceptibility testing (RAST), and a predefined stewardship algorithm for antibiotic optimization. Standard care includes routine culture, MALDI-TOF identification, and CLSI-guided susceptibility testing. Adult patients with confirmed Gram-negative BSIs are enrolled. The primary outcome is the proportion of patients receiving optimal targeted therapy within 24 hours of culture positivity. Secondary outcomes include time to effective therapy, 30-day mortality, hospital length of stay, adverse events, and antibiotic utilization. Analyses will follow an intention-to-treat approach using mixed-effects regression models. Results: As this manuscript presents a study protocol, no clinical outcome data are reported. Patient enrollment and trial implementation are ongoing across participating centers. Conclusion: This rigorously designed pragmatic cluster randomized trial will generate high-quality evidence on whether integrating rapid diagnostics with antimicrobial stewardship improves timely targeted therapy in Gram-negative BSIs, with direct implications for optimizing antimicrobial use and addressing global antimicrobial resistance.